The practice of English language teaching - Harmer, Jeremy (Harlow, England : Pearson Longman, 2007)
A guide to teaching the English language covers such topics as English as world language, methodologies, grouping students, educational technology, lesson planning, testing and evaluation, and learner autonomy.
One side of disc, PAL; other side NTSC.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Foreign speakers